Blockchain for IoT Security Issues - Agung; Febriyanto, Erick; Iskandar, Nur; Alpian Sah, Rizki; Suhendra, Yoke; Andini, Nadila (IAIC Bangun Bangsa, 2022)
In the past couple of years block chain has acquired a parcel of prominence in light of the fact that blockchain is the center innovation of bitcoin. Its use cases are filling in a number of fields like security of Internet of Things (IoT), banking area, enterprises and clinical focuses. Also, IoT has extended its acknowledgment as a result of its organization in brilliant homes and city improvements around the world. Sadly, IoT network gadgets work on restricted registering power with low capacity limit and organization transfer speed. In this manner, there are additional near assaults than other endpoint gadgets, for example, mobile phones, tablets, or PCs. This paper centers around tending to critical security issues of IoT and maps IoT security issues in logical inconsistency of existing arrangements tracked down in the writing. Besides, gifts that are not tackled after execution of blockchain are featured.